Selected ion flow tube mass spectrometry of exhaled breath condensate headspace - Čáp, Petr; Dryahina, Kseniya; Pehal, František; Španěl, Patrik (Rapid communications in mass spectrometry, 2008)
Collection of exhaled breath condensate (EBC) is a relatively simple noninvasive method of breath analysis; however, no data have been reported that would relate concentration of volatile compounds in EBC to their gaseous concentrations in exhaled air. The aim of the study was to investigate which volatile compounds are present in EBC and how their concentrations relate to results of direct breath analysis. Thus, samples of EBC were collected in a standard way from several subjects and absolute levels of several common volatile breath metabolites (ammonia, acetone, ethanol, methanol, propanol, isoprene, hydrogen cyanide, formaldehyde and acetaldehyde) were then determined in their headspace using selected ion flow tube mass spectrometry (SIFT‐MS). Results are compared with those from on‐line breath analyses carried out immediately before collecting the EBC samples. It has been demonstrated that SIFT‐MS can be used to quantify the concentrations of volatiles in EBC samples and that, for methanol, ammonia, ethanol and acetone, the EBC concentrations correlate with the direct breath levels. However, the EBC concentrations of isoprene, formaldehyde, acetaldehyde, hydrogen cyanide and propanol do not correlate with direct breath measurements. Copyright © 2008 John Wiley & Sons, Ltd.